Character Education as a Pillar of Morality for Generation Z : Bibliometric Analysis ( 2019-2024 ) - Defriyadi, Defriyadi; Baharudin, Baharudin; Sai’dy, Sai’dy; Saputra, M. Indra; Shabira , Qonita (Journal of Educational Sciences, 2025)
This research aims to identify and analyze trends in the research on Character Education as a Pillar of Morality for Generation Z (2019-2024) as well as explore opportunities for further research development. Using the Systematic Literature Review (SLR) method, 210 relevant publications were found in the Scopus, Taylor and Francis, and Publish or Perish indexed databases, with 44 documents from the 2019-2024 period selected and analyzed. The literature review process follows PRISMA guidelines to ensure the quality of the results, and the data is analyzed using VOSviewer 1.6.20 software. The results show a steady increase in character education publications as a pillar of generational morality, although there was a small decline in 2022. Indonesia is the country with the largest contribution, followed by Turkey and the United States. This study also found that character education is more effective when integrated with experiential-based learning methods and moral reflection. Qualitative methods are the most commonly used approaches, with the main themes including character education, Islamic religious education, character, and education. This analysis shows the development of character education studies with a more holistic approach that includes Islamic values, culture, and pedagogy to form individuals with high morality.